2012
DOI: 10.1088/0022-3727/45/30/303001
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based devices in terahertz science and technology

Abstract: Graphene is a one-atom-thick planar sheet of a honeycomb carbon crystal. Its gapless and linear energy spectra of electrons and holes lead to nontrivial features such as giant carrier mobility and broadband flat optical response. In this paper, recent advances in graphene-based devices in terahertz science and technology are reviewed. First, the fundamental basis of the optoelectronic properties of graphene is introduced. Second, synthesis and crystallographic characterization of graphene material are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(120 citation statements)
references
References 51 publications
1
116
0
3
Order By: Relevance
“…That finding is in accordance with the experimental results [40]. High carrier mobility has been observed for the multiple-graphene-layer (MGL) structures grown epitaxially on SiC, as well [14,[41][42][43][44]. Growth on the Si-face of SiC results in a lower mobility few-layer graphene, whereas growth on the C-face results in a high mobility multilayer graphene ( ≈ µ 200 000 cm 2 /(Vs)).…”
Section: Full-wave Electromagnetic Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…That finding is in accordance with the experimental results [40]. High carrier mobility has been observed for the multiple-graphene-layer (MGL) structures grown epitaxially on SiC, as well [14,[41][42][43][44]. Growth on the Si-face of SiC results in a lower mobility few-layer graphene, whereas growth on the C-face results in a high mobility multilayer graphene ( ≈ µ 200 000 cm 2 /(Vs)).…”
Section: Full-wave Electromagnetic Analysissupporting
confidence: 89%
“…In addition to its superior structural, mechanical and electrical properties, its electrically, magnetically and optically controllable conductivity makes it a good choice for the realization of tunable or reconfigurable components and devices. Electromagnetic field interaction with graphene at terahertz frequencies has been successfully investigated for a variety of applications including plasmonic antennas, wave modulators, and terahertz lasers [9][10][11][12][13][14][15]. Possible utilization of this controllable conductivity in the millimeter and submillimeter wave range has yet to be addressed more thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…It was theoretically shown that graphene supports surface plasmon polaritons in the terahertz and infrared ranges [7][8][9][10][11][12][13][14][15] and can be a building material for metamaterials, which provide a wider range of electromagnetic properties than continuous graphene. Therefore continuous and structured graphene allows for an ultimate terahertz radiation control resulting in functional devices [16], such as modulators [17][18][19], hyperlenses [20], tunable reflectors, filters, absorbers and polarizers [21][22][23][24]. In this paper we will focus on graphene absorber.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work revealed that ultrafast relaxation of Dirac fermions in Cd 3 As 2 DSM is qualitatively similar to that of graphene [49]. Given the growing interest in driven and non-equilibrium quantum states of matter and the potential of DMs for high-performance optoelectonic devices [17,18], this trend will continue to gain momentum. In this context, we consider the possibility of realizing transient many-body states in optically-pumped 3D DMs.…”
Section: Introductionmentioning
confidence: 99%
“…This can generate optical gain and is promising for THz lasing applications [17]. The lifetime of population inversion in graphene is of the order of 100 fs [19][20][21][22]29].…”
Section: Introductionmentioning
confidence: 99%